2022
DOI: 10.1177/00302228221124358
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Thanatophobia Levels and Attitudes Towards Caregiver Roles Among Nurses in the COVID-19 Period

Abstract: The current study aimed to determine the relationship between fear of death and their caregiver roles in nurses during the COVID-19. The research data were collected with the personal information form, the Thanatophobia scale, the Scale of Nurses’ Attitudes to Their Caregiver Roles (SNACR), the Google Questionnaire Form. Of the nurses participating in the study, 16.1% were diagnosed with COVID-19. The current study found statistically significant differences among the thanatophobia mean scores of the groups co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…Studies show that nurses experience thanatophobia and have moderate or high levels of thanatophobia. The results of this study were similar to other studies [11,20,24].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Studies show that nurses experience thanatophobia and have moderate or high levels of thanatophobia. The results of this study were similar to other studies [11,20,24].…”
Section: Discussionsupporting
confidence: 93%
“…The Thanatophobia Scale mean score of nurses was found to be above the medium level at 31.74 ± 10.08 in this study. There are studies examining the thanatophobia levels of nurses and reported moderate to high levels [11,[20][21][22]. In a qualitative study by De Swardt and Fouche (2017), it was determined that nurses who gave post-mortem care to the deceased in the intensive care unit experienced thanatophobia by confronting the reality of their own death [23].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that nurses experience thanatophobia and have moderate or high levels of thanatophobia. Our results are similar to the results of studies that found moderate levels of thanatophobia [11,20,24].…”
Section: Discussionsupporting
confidence: 92%
“…The Thanatophobia Scale mean score of nurses was moderate at 31.74 ± 10.08 in this study. There have been studies in our country examining the thanatophobia levels of nurses and reported moderate to high levels [11,[20][21][22]. In a qualitative study by De Swardt and Fouche (2017), it was determined that nurses who gave post-mortem care to the deceased in the intensive care unit experienced thanatophobia by confronting the reality of their own death [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation